LES ERAGROSTIS (POACEAE) DU BENIN - HOUINATO, MARCEL ROMUALD BENJAMIN; DELVAUX, Claire; PAUWELS, Luc (My University, 2000)
The genus Eragrostis (Poaceae) in Benin. ? The examination of the herbarium specimens collected in Benin and deposited in BENIN, P, BR and BRLU led us to the identification of 13 species of Eragrostis, for which short description, key, habitat and phy tog
Keywords: Eragrostis